The Relationship Between Organizational Culture And Job Satisfaction Of Hospital Administrative Officers - Pramita Sari, Devi; Fanny, Nabilatul; Nizam Mohd Isa, Khairul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Organizational culture can influence the job satisfaction of hospital administration officers. Based on the preliminary survey, it was discovered that there were 3 hospital administration officers who stated that they were satisfied with their work because of the good organizational culture in the hospital. The aim of this research is to determine the relationship between organizational culture and job satisfaction of hospital administration officers. This research uses analytical research and quantitative methods as well as a cross sectional study approach. The research population and sample were taken by total sampling, namely all hospital administration officers in the hospital, totaling 21 respondents. The research instrument used a questionnaire. Quantitative data analysis used the chi-square relationship test. The results of this research from 21 respondents based on the results of the Chi-Square test showed the significance of p between the independent variable, namely competence and the dependent variable performance, the result was 0.025 (p<0.05), so Ho was rejected and it was stated that there was a relationship. The conclusion is that there is a relationship between organizational culture and job satisfaction of hospital administration officers. Suggestions should provide knowledge of hospital organizational culture to increase job satisfaction for hospital administration officers